A influência da governança corporativa na estrutura de capital e no desempenho financeiro das companhias brasileiras de capital aberto - Savelli, Andrea Décourt (2019)
This paper investigates the relationship between corporate governance (CG) in the capital structure and financial performance of non-financial companies listed in the Brazilian index (IBrX-50) between 2010 and 2017. For this purpose, a review of the literature on corporate governance and capital structure and the collection of necessary data in the Bloomberg, Capital IQ and Economática database was done, which were included in the Stata software. After analyzing 14 models (3 regressions with static panel data and fixed effects and 11 regressions with static panel data and random effects), we can see that the most relevant CG variables are ownership concentration, percentage of independent directors on the board and the dual presence of the CEO. The results evince that the ownweship concentration variable shows a negative relation with the company's performance and positive for the indebtedness, as well as indicates that a higher percentage of independent directors is positively related to a higher indebtedness. The results for CEO dual presence in relation to leverage are mixed and suggest that duality improves performance, which is contrary to expectations. The control variables that present statistical significance are: size, age of incorporation (only for the fixed effect panel and in relation to the performance variables), sales growth (only in relation to leverage variables) and current ratio (in relation to the leverage variables).